Enhancing Reading Comprehension in Education: A Study on the Effec-tiveness of the SQ3R Method - Saputra, Dedi Gunawan; Haddar, Gamar Al (Insan Akademika Publications, 2024)
Reading comprehension is a fundamental skill that underpins academic success and lifelong learning. The SQ3R method, a structured approach that encompasses Survey, Question, Read, Recite, and Review, has long been recognized as a valuable tool for improving reading comprehension. This research aimed to investigate the effectiveness of the SQ3R method in enhancing students' reading comprehension abilities. Pre- and post-assessments of reading comprehension were conducted, and the results were analyzed to assess the impact of the SQ3R method. In addition to quantitative data, qualitative feedback from students was gathered to gain insights into their perceptions of the method. The study revealed a significant increase in reading comprehension scores among students who were exposed to the SQ3R method. The frequency of method usage was positively correlated with improved comprehension outcomes. Longitudinal data showed that the improvements were sustained over time, indicating the method's long-term impact. Students' qualitative feedback echoed the positive quantitative results, underlining increased engagement, a better understanding of complex texts, and improved critical thinking skills. The research findings have significant implications for educators, policymakers, and researchers. Educators are encouraged to incorporate the SQ3R method into teaching practices, promote consistent method usage, and monitor long-term progress. Policymakers are urged to support professional development for educators and ensure access to appropriate educational materials. Future researchers should explore diverse student populations, compare the SQ3R method with alternative strategies, and investigate its adaptability in online learning environments. The SQ3R method has proven to be not only effective but also a powerful asset in education. It equips students with skills and strategies that are essential for understanding and retaining textual content effectively, fostering not only academic success but also a lifelong love for learning.